Unified multimode modelling, stability analysis, and reinforced sliding‐mode design of high‐order buck/boost DC–DC converters for DC energy systems - Chaoyu Dong (Wiley, 2021)
Abstract Unified modelling, analysis, and reinforced sliding‐mode design of a high‐order buck/boost converter are proposed for DC energy systems. The high voltage gain with low current stress on the converter’s circuit components will noticeably improve its performance in DC energy systems. The mathematical model of this multimode converter is established by deploying the averaging state‐space modelling approach and a duty‐ratio constraint‐deriving method. According to the unified multimode model, a reinforced sliding‐mode controller is proposed for this converter, and the sliding surface is designed using the estimated load information. A complete stability analysis of the reinforced sliding‐mode regulated converter system is also carried out. In addition, a hardware‐based comparison study involving the proposed controller and an existing robust sliding‐mode controller is provided to validate the effectiveness of the unified workflow involving modelling, analysis, and regulation design.